Adjusted calculation model of heparin management during cardiopulmonary bypass in obese patients: A randomised controlled trial. Issue 8 (August 2018) - Vienne, Matthias; Haas, Emmanuel; Wipf, Thibaut; Grunebaum, Lelia; Levy, François; Sattler, Laurent; Hoang Minh, Tam; Severac, François; Tacquard, Charles; Collange, Olivier; Mertes, Paul-Michel; Steib, Annick
Abstract : BACKGROUND: Anticoagulation during cardiopulmonary bypass (CPB) is usually adapted to total body weight (TBW). This may be inaccurate in obese patients and lead to heparin overdose with a risk of bleeding. OBJECTIVES: To validate the efficacy and safety of an adjusted calculation model of heparin dosing based on ideal body weight (IBW) rather than TBW in obese CPB patients, with an expected target mean plasma heparin concentration of 4.5 IU ml −1 after onset of CPB in the experimental group. DESIGN: Randomised controlled study. SETTING: University hospital. PATIENTS: Sixty obese patients (BMI ≥ 30 kg m −2 ) scheduled for CPB were included from January to June 2016. INTERVENTIONS: Patients received a bolus dose of unfractionated heparin of either 300 IU kg −1 of TBW or 340 IU kg −1 of IBW before onset of CPB. Additional adjusted boluses were injected to maintain an activated clotting time (ACT) of at least 400 s. MAIN OUTCOME MEASURES: Plasma heparin concentration and ACT were measured at different time points. Total heparin doses and transfusion requirements were recorded. RESULTS: The target heparin concentration of 4.5 IU ml −1 was reached in the IBW group at the onset of CPB and maintained at all time points during CPB. Heparin concentrations were significantly higher in the TBW group after the bolus (6.52 ± 0.97 vs. 4.54 ± 1.13 IU ml −1, P  < 0.001) and after cardioplegia (5.10 ± 1.03 vs. 4.31 ± 1.00 IU ml −1, P  = 0.02). Total heparin doses were significantly higher in the TBW group. Mean ACT was significantly lower in the IBW group but remained over 400 s during CPB. The correlation between heparin and ACT was poor. Peri-operative bleeding and transfusion requirements were comparable. No thrombotic event occurred in the CPB circuit. CONCLUSION: The current IBW-adjusted regimen of heparin administration may be used efficiently in obese CPB patients, thereby avoiding overdose which cannot be accurately assessed by ACT monitoring alone. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT02675647.